The effectiveness of self-healing psychoeducation for fresh graduates experiencing a quarter-life crisis - Karina, Annisa Dian; Djudiyah, Djudiyah (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2026)
Background: Quarter-life crisis is often experienced by fresh graduates and is characterized by uncertainty, decreased self-confidence, and emotional distress. Purpose: To evaluate the effectiveness of self-healing psychoeducation in improving participants' knowledge and preparedness to face the challenges of this transition period. Method: Using a one-group pretest–posttest design, participants completed a 20-item questionnaire before and after sessions that included material delivery, group discussions, case study analysis, and positive self-talk exercises. Results: The t-test results found a t = -7.464 with a significant change (p < .001), followed by an increase in the average score from pretest (M = 10.11) to posttest (M = 15.00), with a mean difference of 4.88 (SD = 1.96). Conclusion: Qualitative findings demonstrated active participation and direct application of self-healing techniques. This program was deemed effective in improving understanding and basic knowledge of facing quarter-life.crisis. Keywords: Fresh Graduates; Psychoeducation; Quarter-Life Crisis; Self-Healing.